KEEFEKTIFAN VIRTUAL LABORATORY TERHADAP HASIL BELAJAR SISWA MATERI LARUTAN PENYANGGA DAN HIDROLISIS - Anisah, Evi; R.S, Sri Mantini; Subroto, Tjahyo (Chemistry in Education, 2013)
The observations in SMA N 1 Demak show the results of student achievement still has not met with the thoroughness studied classical. This research is done to determine the effectiveness of virtual laboratory towards students' achivement about buffer solution and hydrolysis of SMA N 1 Demak. The population is the eleventh grade student of science. Sample was conducted by random sampling technique, obtained a XI IPA 1 as the experimental class get the learning used virtual laboratory and the XI IPA 2 as the control class get the learning used lecture method. To collect the data the writer used documentation, test, observation and questionnaires. The results of the research show that the average students' achivement in experiments class is 80.55 while the control class is 76.82. The percentage thoroughness studied classical of experiment class is 94.74% while the control class is 73.68%. On average students gave positive responses (happy) to each of the indicators contained in the questionnaires. From the analysis can be concluded that virtual laboratory is effective towards the students’ achievement about buffer solution and hydrolysis of SMA N 1 Demak.